Development and Evaluation of a Serum Transfusion Process in the Thorny Devil Stick Insect (Eurycantha calcarata) - Gregory, Taylor M.; Heniff, Ashlyn C.; Gorges, Melinda A.; Lathan, Andrew W.; Lewbart, Gregory A.; Balko, Julie A. (Frontiers in Veterinary Science, 2022)
The thorny devil stick insect (Eurycantha calcarata) is a common invertebrate maintained under human care. Blood (hemolymph) transfusions are a widely used therapeutic tool in other species, but investigation in terrestrial arthropods remains scarce. Study objectives were development and evaluation of a serum transfusion process in the thorny devil stick insect. Twenty-five clinically healthy adult insects (9.9–23.0 g) were enrolled and baseline body weights were collected. Hemolymph collection was not successful in males, thus, all were recipient only (n = 12, MR). Females were divided into donor (n = 4, FD) or donor and recipient (n = 9, FDR) groups. Females were manually restrained and up to 1 mL of hemolymph was collected from the abdominal segment caudal to the proximal hindlimb using an 18 g hypodermic needle and passive collection via gravity. Hemolymph was quantified, centrifuged, and the serum separated. Insects were then injected superficially at the lateral aspect of the abdomen with 0.01 mL/g FD serum (MR), lactated Ringer's solution (LRS) equal to collected hemolymph volume (FD), or a combination of FDR serum and LRS equal to collected hemolymph volume (FDR). Response to stimulation, surface temperature, and righting reflex and mortality were serially assessed for up to 24 h and 7 days, respectively, following injection. In FD, median (range) injected LRS dose was 0.04 (0.03–0.06) mL/g. In FDR, median (range) injected serum, LRS, and combined serum and LRS dose was 0.03 (0.02–0.04), 0.01 (0–0.04), and 0.04 (0.02–0.06) mL/g, respectively. A mild temperature increase (maximum +2.9°C) (MR n = 10, FD n = 3, FDR n = 8) and delayed righting reflex (MR n = 4, FD n = 3, FDR n = 7) occurred in a subset of insects following injection. Two deaths occurred at 2 min (n = 1, FDR) and 96 h (n = 1, FD) post-injection. This is the first report of serum transfusions in thorny devil stick insects, and while largely successful, minor to severe transfusion reactions may occur.